2016
DOI: 10.46989/001c.20795
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Time after Hormonal Stimulation on Milt Properties in Waigieu Seaperch Psammoperca waigiensis

Abstract: As from January 2010 The Israeli Journal of Aquaculture-Bamidgeh (IJA) will be published exclusively as an on-line Open Access (OA) quarterly accessible by all AquacultureHub (http://www.aquaculturehub.org) members and registered individuals and institutions. Please visit our website (http://siamb.org.il) for free registration form, further information and instructions. This transformation from a subscription printed version to an on-line OA journal, aims at supporting the concept that scientific peer-reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Some pathogen and strains can be treated by high level of AA at the same time increase immunity resistance of several fish (Patra 2008, Dawood and Koshio 2018) [8,28] . Several published studies have demonstrated an enhanced immune response of fish through dietary supplementation with vitamin C (Landolt 1989, Dawood and Koshio 2018) [8,17] , feeding supplemented feed to Waigieu sea perch in its seasonality reproductive which are from April to September (Pham et al 2012) [29] showed good performance based that estimation of gonadosomatic index (GSI) and histological shown preferred spawning season is from April to October (Shimose and Tachihara 2006) [33] , but for induction spawning hormonal stimulation can be collected after 48 hours with limited dose in order to allow efficacy of milt properties (Le and Brown 2016, Le et al 2014) [18,19] . Waigieu seaperch brood stock can be well managed thought sperm cryopreservation by provision of hybrid breeding and its reproduction (Le and Pham 2017) [20] .…”
Section: Introductionmentioning
confidence: 99%
“…Some pathogen and strains can be treated by high level of AA at the same time increase immunity resistance of several fish (Patra 2008, Dawood and Koshio 2018) [8,28] . Several published studies have demonstrated an enhanced immune response of fish through dietary supplementation with vitamin C (Landolt 1989, Dawood and Koshio 2018) [8,17] , feeding supplemented feed to Waigieu sea perch in its seasonality reproductive which are from April to September (Pham et al 2012) [29] showed good performance based that estimation of gonadosomatic index (GSI) and histological shown preferred spawning season is from April to October (Shimose and Tachihara 2006) [33] , but for induction spawning hormonal stimulation can be collected after 48 hours with limited dose in order to allow efficacy of milt properties (Le and Brown 2016, Le et al 2014) [18,19] . Waigieu seaperch brood stock can be well managed thought sperm cryopreservation by provision of hybrid breeding and its reproduction (Le and Pham 2017) [20] .…”
Section: Introductionmentioning
confidence: 99%